Implementasi Metode Mobile D pada E-Posyandu berbasis Android sebagai Alat Literasi dalam Mencegah Stunting Anak Usia Dini - Arifin, Rita Wahyuni; Nurul Alfian, Ari; Inayah Ainina Mawardi (LPPM POLITEKNIK LP3I BANDUNG, 2024)
Stunting is a worldwide health problem that impacts children's physical growth and development. According to the latest Indonesian Nutrition Status Survey (SSGI), the stunting rate in Indonesia will reach 21.6% by 2022. Due to its high prevalence, stunting is a major concern. This condition can affect the future of society, the quality of life and the productivity of children. Among the factors causing stunting are inadequate nutrition, unhealthy pregnancies, improper feeding methods, lack of hygiene and sanitation, economic and social factors, infections and chronic diseases, lack of access to health services, and lack of knowledge about the importance of maintaining health for growing children. To solve this problem, an Android-based application is needed that can be accessed anywhere. In this research, the method used is Mobile D consisting of five phases: exploration, Initialization, Production, Stabilization, and System Testing and Fix. It is hoped that the E-Posyandu Application can improve community access to basic health services. With this application, the danger of stunting can be avoided because pregnant women, mothers of toddlers, and other posyandu members can easily access information about child growth and development info, immunization info at each developmental period, info on the location of the nearest RSIA, and complementary food information for toddlers over the age of 6 (six).